ANALISIS LAJU UAP OLEH BOILER DENGAN KAPASITAS 9 LITER AIR DAN 10KG SAMPAH ORGANIK PADA PLTSa - Riyan Bhaskara Surya A, I.B; Indra Partha, Cok Gede; Janardana, I G N (Program Studi Teknik Elektro UNUD, 2023)
The island of Bali is geographically surrounded by the ocean, therefore its coastal areas are often visited by garbage coming from the sea. Garbage is one of the most serious problems in the coastal areas of the beaches on the island of Bali, Biaung Beach located in Kesiman Kertalangu Village, East Denpasar is one of the beaches that is often visited by garbage from the sea, where the garbage per day reaches 38 kg / day. The purpose of this study was to determine the steam pressure generated by a boiler with a capacity of 9 liters of water and 10 kg of organic waste in a Waste Power Plant (PLTSa). The descriptive quantitative method used in this study is to determine the steam rate coming out of the boiler with 53.26% organic waste moisture content in the PLTSa Prototype using a 13.6 kilogram freon tube and 3 bar vapor pressure, a power of 209 watts is obtained.